You are on page 1of 4

Calculus 081 Unit 7

BINOMIAL SERIES AND ARC LENGTH
This unit corresponds to Sections 11.11 and 8.1 of Stewart’s textbook.
Copyright c 2002 by the Department of Mathematics, University of Western Ontario.
You probably know that if k is a positive integer and a and b are real numbers,
then
(a + b)
k
=
k

n=0
_
k
n
_
a
k−n
b
n
,
where the binomial coeﬃcient
_
k
n
_
(“k choose n ”) is deﬁned by the formula
_
k
n
_
=
k(k −1) . . . (k −n + 1)
n(n −1) . . . 1
=
k!
n!(n −k)!
for n ≥ 1, and
_
k
0
_
= 1.
What if k is not a positive integer? It may be shown that for any real number
k and |x| < 1,
(1 + x)
k
= 1 + kx +
1
2
k(k −1)x
2
+
1
3!
k(k −1)(k −2)x
3
+· · · =

n=0
_
k
n
_
x
n
,
where the coeﬃcients
_
k
n
_
are deﬁned as above:
_
k
n
_
=
k(k −1) . . . (k −n + 1)
n(n −1) . . . 1
for n ≥ 1, and
_
k
0
_
= 1.
This series is called the binomial series.
Let us explain brieﬂy how this is done (you should work out the details of
each step). First of all, how do we come up with this series? It is simply the
Maclaurin series of the function f(x) = (1+x)
k
. Using the Ratio Test, we see
that its radius of convergence is 1, so its sum is a function g on the interval
(−1, 1). How do we know that f = g? The question of whether or not a
function is the sum of its Maclaurin series is generally too hard for us to tackle
in this course, but here a little trick does the job. Diﬀerentiating the binomial
series, we see that its sum g satisﬁes the diﬀerential equation g

(x) =
kg(x)
1 + x
.
Using this, we can easily show that the function h(x) = g(x)(1 + x)
−k
has
1
derivative zero, so it is constant on (−1, 1). Since h(0) = 1, we ﬁnally get
g(x) = (1 + x)
k
on (−1, 1).
Example. Let us ﬁnd a power series expansion for the function f(x) =
x/(1 −x)
2
centred at zero. Using the binomial series, we get
f(x) =
x
(1 −x)
2
= x(1 −x)
−2
= x

n=0
_
−2
n
_
(−x)
n
=

n=0
(−1)
n
(−2)(−3) . . . (−n −1)
n!
x
n+1
=

n=0
(n + 1)x
n+1
=

n=1
nx
n
for |x| < 1. From this we can calculate a nice little inﬁnite sum:

n=1
n
2
n
= f(
1
2
) =
1
2
(1 −
1
2
)
2
= 2.
Arc length. We now turn to the subject of calculating lengths of curves.
For now we shall only consider graphs of functions, but later we’ll study more
general curves.
Let f be a continuous function on the interval [a, b]. We divide the interval
into n subintervals of equal length ∆x = (b −a)/n with endpoints x
0
= a <
x
1
< x
2
< · · · < x
n
= b. Let P
i
be the point (x
i
, y
i
), y
i
= f(x
i
), on the graph
of f.
0
–2 –1 1 2
x
Figure 1: f(x) = x
2
with a = −2, b = 2, and n = 4.
The graph of f is approximated by the broken line P
0
P
1
. . . P
n
. We deﬁne
the length of the graph as the limit of the lengths of these broken lines as
n →∞, if the limit exists.
2
Suppose f has a continuous ﬁrst derivative on [a, b]. By Pythagoras, the
length of the line segment P
i−1
P
i
is
_
(x
i
−x
i−1
)
2
+ (y
i
−y
i−1
)
2
=
_
(∆x)
2
+ (∆y
i
)
2
= ∆x
¸
1 +
_
∆y
i
∆x
_
2
.
By the Mean Value Theorem, this equals
∆x
_
1 + f

(x

i
)
2
for some x

i
between x
i−1
and x
i
, so by the deﬁnition of the deﬁnite integral,
the length of the graph is
L = lim
n→∞
n

i=1
∆x
_
1 + f

(x

i
)
2
=
_
b
a
_
1 + f

(x)
2
dx =
_
b
a
¸
1 +
_
dy
dx
_
2
dx.
The arc length function
s(x) =
_
x
a
_
1 + f

(t)
2
dt
gives the length of the graph from a up to x. By the Fundamental Theorem
of Calculus,
s

(x) =
_
1 + f

(x)
2
or
ds
dx
=
¸
1 +
_
dy
dx
_
2
.
This is sometimes written as
(ds)
2
= (dx)
2
+ (dy)
2
.
Examples. (1) Let us ﬁnd the length of the curve y = ln x for 1 ≤ x ≤

3.
We have dy/dx = 1/x, so
¸
1 +
_
dy
dx
_
2
=
_
1 +
1
x
2
=

1 + x
2
x
.
The length L of the curve is the integral of this from 1 to

3. To calculate this
integral, it is natural to try the trigonometric substitution x = tan θ, which
3
works if followed by the substitution u = sec θ. Let us do both substitutions
at once and take u =

1 + x
2
. Then du =
x

1 + x
2
dx, so
_

1 + x
2
x
dx =
_

1 + x
2
x

1 + x
2
x
du =
_
1 + x
2
x
2
du =
_
u
2
u
2
−1
du.
Note that the u-limits corresponding to the x-limits 1 and

3 are

2 and 2.
Using partial fractions, starting with long division, we get
L =
_

3
1

1 + x
2
x
=
_
2

2
u
2
u
2
−1
du =
_
2

2
_
1 +
1
2
u −1

1
2
u + 1
_
du
=
_
u +
1
2
ln(u −1) −
1
2
ln(u + 1)
¸
2

2
= 2 −
1
2
ln 3 −

2 +
1
2
ln(

2 −1) −
1
2
ln(

2 + 1)
= 2 −

2 + ln(

2 −1) −
1
2
ln 3.
(2) Let us set up an integral for the length of the ellipse
x
2
a
2
+
y
2
b
2
= 1,
where 0 < b ≤ a. We need dy/dx. Diﬀerentiating the formula of the ellipse
implicitly, we get
1
a
2
2x +
1
b
2
2y
dy
dx
= 0, so
dy
dx
= −
b
2
a
2
x
y
, and, as you should
verify,
1 +
_
dy
dx
_
2
= · · · =
a
2

2
x
2
a
2
−x
2
,
where = 1−
b
2
a
2
∈ [0, 1) is the eccentricity of the ellipse. Hence, the length
of the ellipse is
L = 2
_
a
−a
_
a
2

2
x
2
a
2
−x
2
dx.
This is a so-called elliptic integral. How to evaluate it is beyond the scope of
this course.
4